From apocalypticism to Merkabah mysticism : studies in the Slavonic Pseudepigrapha - Orlov, Andrei A., 1960- (Supplements to the Journal for the study of Judaism, 2007)
The present volume contains essays dealing with the Second Temple Jewish traditions and documents preserved solely in their Slavonic translations. It examines these Slavonic pseudepigraphical materials in the context of their mediating role in the development of early Jewish mystical traditions from Second Temple apocalypticism to Merkabah mysticism attested in rabbinic and Hekhalot materials. The book represents the first attempt to study Slavonic pseudepigrapha collectively as a unique group of texts that share common theophanic and mediatorial imagery crucial for the development of early Jewish mysticism. The study demonstrates that mediatorial traditions of the exalted patriarchs and prophets played an important role in facilitating the transition from apocalypticism to early Jewish mysticism.